1996
DOI: 10.1002/(sici)1099-0488(199612)34:17<2953::aid-polb8>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

X-ray scattering and thermal analysis study of the effects of molecular weight on phase structure in blends of poly(butylene terephthalate) with polycarbonate

Abstract: Blends of Poly(butylene terephthalate), PBT, with Polycarbonate, PC, were studied for a range of molecular weights and blend compositions. Blends were available in PBT/PC compositions 80/20 and 40/60, and with Mw designated by H (high) or L (low). Samples were prepared by melt crystallization, or by cold crystallization following a rapid quench from the melt. Addition of PC reduces the crystallization kinetics of PBT so that the resulting crystals are more perfect than those which form in the homopolymer. Degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…Considerable attention has been given to the origins of miscibility and to binary polymer-polymer phase diagrams. It is usually observed that high molar mass polymer pairs, showing partial miscibility, exhibit phase diagrams that indicate a lower critical solution temperature (LCST) [2,[45][46][47]. In a polymer blend that exhibits LCST behaviour, the miscibility is higher at low temperatures.…”
Section: Thermodynamic Requirements For Miscibility In Multicomponentmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable attention has been given to the origins of miscibility and to binary polymer-polymer phase diagrams. It is usually observed that high molar mass polymer pairs, showing partial miscibility, exhibit phase diagrams that indicate a lower critical solution temperature (LCST) [2,[45][46][47]. In a polymer blend that exhibits LCST behaviour, the miscibility is higher at low temperatures.…”
Section: Thermodynamic Requirements For Miscibility In Multicomponentmentioning
confidence: 99%
“…Other approaches exist to determine x for polymer blends. These include the use of the glass transition temperature (T g ) [59] and the use of melting temperature (T m ) [13,46], based on the effect of miscibility on these characteristic temperatures.…”
Section: Interaction Parameters From Polymer Solution Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…These include phosphates and phosphoruscontaining acids. 30,40 Stabiliser systems based on phosphoric acid can lead to a decrease of the hydrolytic stability of the blend. Di-n-octadecyl 44 and triphenyl phospite 35 are widely used as efficient transesterification inhibitors.…”
Section: The Transesterification Reaction Between Pc and Pbtmentioning
confidence: 99%
“…The crystallisation temperature of PBT is approximately 180 uC. 19 The crystallinity of the PBT in PC-PBT blends has been determined by Hanrahan et al 30 and by Cheng et al 30 to be 26 to 38%. A maximum degree of PBT crystallisation of 40% in these blends was observed by Ratzsch et al 28 The overall degree of crystallinity is greater in cold-crystallised blends than in melt crystallised blends.…”
Section: Crystallisation Properties Of Pc-pbt Blendsmentioning
confidence: 99%